2022
DOI: 10.31234/osf.io/wmucy
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Progressing, not regressing: a possible solution to the problem of regression to the mean in unconscious processing studies

Abstract: How convincing is current evidence for unconscious processing? Recently, a major criticism suggested that this evidence might be fully explained by a mere statistical phenomenon: regression to the mean (RttM). Since excluding participants based on an awareness assessment is a common practice in such studies, this post-hoc data selection might evoke RttM and lead to false effects that are driven by aware participants wrongfully classified as unaware. Here, we examined this criticism using both simulations and d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Even with sufficient power, post‐hoc exclusion of participants/trials from the final analysis (i.e. excluding trials rated as ‘visible’ or excluding participants with above‐chance awareness) has been criticized on the ground that it leads to the regression to the mean (Rothkirch et al, 2022; Shanks, 2017; Yaron et al, 2022), which underestimates true awareness. Awareness measures are prone to measurement error (noise; Vadillo et al, 2022; Yaron et al, 2022), so the observed awareness score would be a combination of the true awareness score plus some measurement error (Rothkirch et al, 2022).…”
Section: Methodological Issues In the Field Of Subliminal Processingmentioning
confidence: 99%
See 4 more Smart Citations
“…Even with sufficient power, post‐hoc exclusion of participants/trials from the final analysis (i.e. excluding trials rated as ‘visible’ or excluding participants with above‐chance awareness) has been criticized on the ground that it leads to the regression to the mean (Rothkirch et al, 2022; Shanks, 2017; Yaron et al, 2022), which underestimates true awareness. Awareness measures are prone to measurement error (noise; Vadillo et al, 2022; Yaron et al, 2022), so the observed awareness score would be a combination of the true awareness score plus some measurement error (Rothkirch et al, 2022).…”
Section: Methodological Issues In the Field Of Subliminal Processingmentioning
confidence: 99%
“…excluding trials rated as ‘visible’ or excluding participants with above‐chance awareness) has been criticized on the ground that it leads to the regression to the mean (Rothkirch et al, 2022; Shanks, 2017; Yaron et al, 2022), which underestimates true awareness. Awareness measures are prone to measurement error (noise; Vadillo et al, 2022; Yaron et al, 2022), so the observed awareness score would be a combination of the true awareness score plus some measurement error (Rothkirch et al, 2022). Positive error would more likely result in a larger observed score (since you are ‘adding’ to the true score), and likewise negative error (‘subtracting’ from the true score) often leads to a smaller observed score.…”
Section: Methodological Issues In the Field Of Subliminal Processingmentioning
confidence: 99%
See 3 more Smart Citations